Artistic gymnastics mirror teaching approach efficacy for improving interpersonal skills of college students. Issue 5 (3rd September 2022) - Zhou, Zan; Tian, Haibo; Luo, Siwei; Wang, Yao; Shi, Dan
Abstract : This study aimed at improving the interpersonal skills of college students through an intervention of artistic gymnastics mirror teaching approach. Following a longitudinal study quasi-experimental design, 30 students were randomly assigned to the artistic gymnastics' intervention, and 30 students were assigned to the standard curriculum. Both groups completed a measure of interpersonal skills before and after the intervention. Repeated measures analysis results indicated that the artistic gymnastics intervention group showed significant improvement in interpersonal skills of communication, interpersonal integration, and expressive understanding as compared to the students who were assigned to the standard curriculum. These findings provide preliminary evidence for using mirror teaching for college students to improve their interpersonal skills. Further, the wider adoption of mirror teaching by instructors would serve as a student communication distress prevention strategy.